Bowel function after surgery in male children with complicated anorectal malformations - Zhao, Hanbin; Cao, Jian; Hou, Jinping; Shi, Yuan; Wang, Yi (Frontiers in Pediatrics, 2025)
BackgroundSome children may experience defecation dysfunction following surgery for anorectal malformations. This study evaluated the long-term functional outcomes and influencing factors in male children with complicated anorectal malformations (ARMs).MethodsWe retrospectively analyzed the clinical data of male children with complicated ARMs who underwent staged surgeries in our hospital from 2013 to 2016. Data collected included ARM type, perianal muscle development, anorectal manometry findings, lumbosacral MRI findings and the intervals between the first and third operation. Bowel function after the operation was assessed by questionnaire (modified Rintala score). Logistic regression analysis was used to analyze the influencing factors of prognosis.ResultsFifty-eight children were included in this study, with a median age at PSARP of 6.7 months. Bowel function did not differ based on anorectal malformations subtype (p = 0.212). Perianal muscle development was significantly associated with bowel function (p = 0.023, rs = 0.297). Fifty-one children received anorectal manometry, which showed no significant differences in anal resting pressure (ARP) among the different bowel function groups(p = 0.666). Rectoanal inhibitory reflex (RAIR) was present in 3/12 (25%), 10/36 (27.8%), and 1/3 (33.3%) children in the normal, good, and fair groups, respectively (p = 0.781). Bowel function was significantly worse in children with spinal cord anomalies than in children with normal spinal cord (OR = 4.651, p = 0.032). Stooling level worsened with increasing intervals between the first and third operation (OR = 3.808, p = 0.039).ConclusionThe incidence of spinal cord abnormalities in male children with complicated ARMs was high. Spinal cord anomalies and long intervals of the staging operation increased the risk of poor postoperative outcomes.